2007
DOI: 10.3141/2034-12
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bus Priority Lane as Countermeasure for Congestion

Abstract: The main objective of this research is to identify the effectiveness of the bus priority lane in Shizuoka City, Japan, as a countermeasure for traffic congestion. Shizuoka City, the capital of Shizuoka Prefecture in Japan, suffers from frequent traffic congestion. To tackle this problem, authorities of Shizuoka City tested a pilot project that implemented bus rapid transit (BRT) strategies. This project included a bus priority lane along a 3-km segment and a bus priority signal system. The project data were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 1 publication
(1 reference statement)
1
21
0
1
Order By: Relevance
“…Both Viegas et al (2007) and Currie & Lai (2008) concluded that driver compliance with the intermittent bus lane restrictions was high and also that intermittent sharing strategies improved bus service without significantly degrading car traffic. Sakamoto et al (2007) also field tested the idea of allowing cars to use a bus priority lane when buses are not present in Shizuoka, Japan. These authors not only observed reduced travel times for buses, but also a reduction in car congestion.…”
Section: Bus Priority Strategies Targeted To Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Viegas et al (2007) and Currie & Lai (2008) concluded that driver compliance with the intermittent bus lane restrictions was high and also that intermittent sharing strategies improved bus service without significantly degrading car traffic. Sakamoto et al (2007) also field tested the idea of allowing cars to use a bus priority lane when buses are not present in Shizuoka, Japan. These authors not only observed reduced travel times for buses, but also a reduction in car congestion.…”
Section: Bus Priority Strategies Targeted To Linksmentioning
confidence: 99%
“…However, Currie & Lai (2008) reported that during the field experiments conducted for intermittent lanes in Melbourne, Australia no increase in accidents was observed. While reporting some initial confusion among drivers in the field experiment of intermittent lanes in Shizuoka, Japan, Sakamoto et al (2007) stated that the drivers were behaving as expected by the end of the experiment (which lasted 5 days). The authors also reported that as a result of a survey conducted on residents who live close to field experiment site, the dissatisfaction rate was only 10%.…”
Section: Dissertation Findingsmentioning
confidence: 99%
“…Takeshita et al (2007) assessed an exclusive median bus lane system in Nagoya of Japan. Bus lane systems were also studied comprehensively in the research studies of (Shalaby and Soberman,1994;Shalaby,1999;Seo et al, 2005;Sakamoto et al, 2007;Arasan and Vedagiri, 2008;Zhu et al, 2010;Tian and Jia, 2016;Chen et al, 2016;Cesme et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…36-48, for examples). a) Electronic address: jorge.villalobos@unibague.edu.co Among these researchers, there seems to be an interest on the impact of exclusive-lines on the dynamics of buses; [49][50][51] however, most of the cited articles are concerned with the evaluation of the single lines as viable strategies, and not on characterizing the different dynamics that can occur.…”
Section: Introductionmentioning
confidence: 99%